2019
DOI: 10.1002/per.2220
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Loneliness across the Lifespan: A Meta–Analysis

Abstract: Different theoretical contentions on gender differences in loneliness exist, often including the emergence of gender differences in particular developmental periods. To explain those ideas, the current meta–analysis synthesizes the available evidence on gender differences in loneliness across the lifespan. Three–level meta–analyses were conducted with 751 effect sizes, covering 399,798 individuals (45.56% males). Results showed a close–to–zero overall effect ( g = 0.07). Most examined moderators were non–signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
190
9
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(226 citation statements)
references
References 63 publications
20
190
9
7
Order By: Relevance
“…Intriguingly, these results are in line with previous evidence suggesting that gender differences in altruistic behaviors might be related to differences in feelings of loneliness. In particular, consistent with previous evidence (e.g., 55 , 56 , but see also: 57 ), in the current work, women reported to feel lonelier than men and such difference in feelings of loneliness might explain why women tend to be more altruistic than men 58 . However, it has to be noted that differences between men and women in both reported feelings of loneliness and altruistic behaviors might be due to internalized sex roles expectations.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, these results are in line with previous evidence suggesting that gender differences in altruistic behaviors might be related to differences in feelings of loneliness. In particular, consistent with previous evidence (e.g., 55 , 56 , but see also: 57 ), in the current work, women reported to feel lonelier than men and such difference in feelings of loneliness might explain why women tend to be more altruistic than men 58 . However, it has to be noted that differences between men and women in both reported feelings of loneliness and altruistic behaviors might be due to internalized sex roles expectations.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the correlation based on the small sample size of 22 was far from decisive. Although Study 2 (N = 243) confirmed the negative association between loneliness and relationship value upregulation, it might have been still underpowered to detect some moderation effects, such as gender difference: A recent metaanalytic review revealed that gender difference in loneliness is small (Hedge's g = .08; Maes et al, 2019). Given these problems associated with the current study, we refrain from drawing any strong conclusions about the loneliness-insensitivity to commitment signal association.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies report that females are lonelier than males [19,20], whereas others show that loneliness is more prevalent among males [13,21]. However, a recent meta-analysis found no gender differences in loneliness among adults [22] In addition to demographic factors, several social factors have been associated with loneliness including living alone [16], having a smaller social network [23], lacking social support and low frequency of social contacts, e.g. seeing friends [24].…”
Section: Introductionmentioning
confidence: 99%